Imaging of the temporal bone - Loevner, Laurie A.; Swartz, Joel D. (Thieme, 2009)
Offers comprehensive coverage of various imaging strategies for the evaluation of disease processes affecting the temporal bone. This book features a practical 'how-to' chapter that presents imaging modalities, technical parameters, and major clinical indications.